Systematic Review of High Probability Requests in K-12 Settings: Examining the Evidence Base. (November 2019) - Common, Eric Alan; Bross, Leslie Ann; Oakes, Wendy Peia; Cantwell, Emily Dawn; Lane, Kathleen Lynne; Germer, Kathryn Ann
We conducted this systematic review to classify the evidence-base status for high-probability request sequence (HPRS) as a strategy to improve students' behavioral outcomes in general and special education settings across the K-12 continuum. Specifically, the purpose of this review was to determine whether HPRS could be classified as an evidence-based practice according to Council for Exceptional Children's Standards for Evidence-Based Practices in Special Education employing a modified, weighted coding scheme specifying methodologically sound studies as meeting 80% or more of components across quality indicators (QIs). Two of the 22 included studies met all QIs, and 16 studies met or exceeded our 80% weighted criterion. Based on this body of evidence, we classified HPRS in K-12 school settings as potentially evidence based . We offer a discussion of educational implications, limitations, and future directions.